Wearables als unterstützendes Tool für den Paradigmenwechsel in der Versorgung von Parkinson Patienten - Thun-Hohenstein, Caroline; Klucken, Jochen (Klinische Neurophysiologie, 2021)
Wearables are portable sensors that are suitable for collecting data on functional disturbances in patients with Parkinson's disease and are used for prevention, prediction, diagnosis and therapy. In research applications, they increase the reliability of the collected data and represent better study endpoints than traditional subjective and non-quantitative ratings and self-report scales. In this study, we examine motor symptoms such as tremor, bradykinesia and gait disturbances as well as non-motor symptoms. Home diagnostics can be used to examine the patient's condition in real life, monitor therapy, improve adherence, and check compliance. Additionally, wearables can be used in interventions such as cueing, gamification or coaching in order to improve symptoms. Transfer from laboratory conditions to everyday life at home is a medical-technical challenge, optimized care models have to be developed and the actual benefit for the individual patient needs to be demonstrated in further studies.
CRIS-Team Scopus Importer:2021-03-19
Keywords: care effect; gait analysis; Parkinson's disease; value-based medicine; wearables